2008
DOI: 10.2337/db07-1187
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of AMP-Activated Protein Kinase α2 Activity Exacerbates Insulin Resistance Induced by High-Fat Feeding of Mice

Abstract: OBJECTIVE-We determined whether muscle AMP-activated protein kinase (AMPK) has a role in the development of insulin resistance.RESEARCH DESIGN AND METHODS-Muscle-specific transgenic mice expressing an inactive form of the AMPK ␣2 catalytic subunit (␣2i TG) and their wild-type littermates were fed either a high-fat (60% kcal fat) or a control (10% kcal fat) diet for 30 weeks.RESULTS-Compared with wild-type mice, glucose tolerance in ␣2i TG mice was slightly impaired on the control diet and significantly impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
78
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 57 publications
12
78
2
3
Order By: Relevance
“…Similar studies in long-term AICAR treatment of rats reported reduced metabolic disturbances and lowered blood pressure in rats displaying features of the insulin resistance syndrome [51]. Finally, muscle-specific ablation of AMPKα 2 activity has been shown to exacerbate insulin resistance induced by high-fat feeding of mice [52].…”
Section: Discussionmentioning
confidence: 69%
“…Similar studies in long-term AICAR treatment of rats reported reduced metabolic disturbances and lowered blood pressure in rats displaying features of the insulin resistance syndrome [51]. Finally, muscle-specific ablation of AMPKα 2 activity has been shown to exacerbate insulin resistance induced by high-fat feeding of mice [52].…”
Section: Discussionmentioning
confidence: 69%
“…2-DG, 2-deoxy-glucose While this manuscript was in preparation, Fujii et al [31] demonstrated that mice on a FVB background overexpressing a muscle-specific KD AMPKα2 Asp157Ala mutation develop more severe muscle insulin resistance after 30 weeks on a high-fat diet with 60% of energy from fat (compared with 12 weeks of a high-fat diet with 45% of energy from fat, as used in the current study), an effect which occurred independently of increases in muscle lipids. The difference between our findings and those of Fujii et al [31] may be related to the use of different diet protocols, but probably more importantly, to the use of different mouse strains, as the FVB strain of mice is known to be resistant to the effects of high-fat diet-induced obesity compared with mice on a C57/BL6 background [32] as used in the current study. But the fact that the genotype effect occurred 26 weeks later than the first evidence of glucose intolerance suggests that AMPK did not have a primary role in the development of insulin resistance, as was recognised by Fujii el al.…”
Section: Discussionmentioning
confidence: 99%
“…But the fact that the genotype effect occurred 26 weeks later than the first evidence of glucose intolerance suggests that AMPK did not have a primary role in the development of insulin resistance, as was recognised by Fujii el al. [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult male C57BL/6 mice were purchased from Beijing Vital River Laboratory Animal Technology (Beijing, China). As previously reported, seven-week-old mice were randomly divided into two groups [31]: one group received standard rodent chow (10% energy from fat; Beijing HFK Bioscience, Beijing, China) and the other group received a high-fat diet (HFD; 60% energy from fat; rodent diet D12492, Research Diets, New Brunswick, NJ, USA). Animals were fed a HFD or chow diet for 30 weeks.…”
Section: Methodsmentioning
confidence: 99%